Automated Testing of Java Web Applications - Kalmo, Märt (My University, 2009)
The thesis analyses the profitability of doing automated testing on web applications. It starts with laying out the problems with web application testing and suggests some solutions to overcome them. These ideas about addressing web application testing are combined into a notion of testing framework for web application development. This framework is realized as a part of the thesis and its actual effectiveness is evaluated through using the framework in an experiment. The essence of this experiment is building a sample application twice – once with the support of testing framework and once without it. The performance of both trials will be measured and the findings analyzed. The thesis concludes with the discussion about whether the data gathered from the experiment supports the goal of the thesis.
Keywords: Programvaruteknik; Software Engineering